<meta http-equiv="refresh" content="1; url=/nojavascript/">

# 3.8: Tangent Sum and Difference Formulas

Difficulty Level: At Grade Created by: CK-12
0%
Progress
Practice Tangent Sum and Difference Formulas
Progress
0%

Suppose you were given two angles and asked to find the tangent of the difference of them. For example, can you compute:

tan(12040)\begin{align*}\tan (120^\circ - 40^\circ)\end{align*}

Would you just subtract the angles and then take the tangent of the result? Or is something more complicated required to solve this problem? Keep reading, and by the end of this Concept, you'll be able to calculate trig functions like the one above.

### Guidance

In this Concept, we want to find a formula that will make computing the tangent of a sum of arguments or a difference of arguments easier. As first, it may seem that you should just add (or subtract) the arguments and take the tangent of the result. However, it's not quite that easy.

To find the sum formula for tangent:

tan(a+b)tan(a+b)=sin(a+b)cos(a+b)=sinacosb+sinbcosacosacosbsinasinb=sinacosb+sinbcosacosacosbcosacosbsinasinbcosacosb=sinacosbcosacosb+sinbcosacosacosbcosacosbcosacosbsinasinbcosacosb=sinacosa+sinbcosb1sinasinbcosacosb=tana+tanb1tanatanbUsing tanθ=sinθcosθSubstituting the sum formulas for sine and cosineDivide both the numerator and the denominator by cosacosbReduce each of the fractionsSubstitute sinθcosθ=tanθSum formula for tangent

In conclusion, tan(a+b)=tana+tanb1tanatanb\begin{align*}\tan(a+b) = \frac{\tan a + \tan b}{1 - \tan a \tan b}\end{align*}. Substituting b\begin{align*}-b\end{align*} for b\begin{align*}b\end{align*} in the above results in the difference formula for tangent:

tan(ab)=tanatanb1+tanatanb

#### Example A

Find the exact value of tan285\begin{align*}\tan 285^\circ\end{align*}.

Solution: Use the difference formula for tangent, with 285=33045\begin{align*}285^\circ = 330^\circ - 45^\circ\end{align*}

tan(33045)=tan330tan451+tan330tan45=3311331=3333=33333+33+3=963393=12636=23

To verify this on the calculator, tan285=3.732\begin{align*}\tan 285^\circ = -3.732\end{align*} and 23=3.732\begin{align*}-2 -\sqrt{3} = -3.732\end{align*}.

#### Example B

Verify the tangent difference formula by finding tan6π6\begin{align*}\tan \frac{6\pi}{6}\end{align*}, since this should be equal to tanπ=0\begin{align*}\tan \pi = 0\end{align*}.

Solution: Use the difference formula for tangent, with tan6π6=tan(7π6π6)\begin{align*}\tan \frac{6\pi}{6} = \tan (\frac{7 \pi}{6} - \frac{\pi}{6})\end{align*}

tan(7π6π6)=tan7π6tanπ61+tan7π6tanπ6=262612626=01236=03436=0

#### Example C

Find the exact value of tan165\begin{align*}\tan 165^\circ\end{align*}.

Solution: Use the difference formula for tangent, with 165=22560\begin{align*}165^\circ = 225^\circ - 60^\circ\end{align*}

tan(22560)=tan225tan601+tan225tan60=13113=1

### Guided Practice

1. Find the exact value for tan75\begin{align*}\tan 75^\circ\end{align*}

2. Simplify tan(π+θ)\begin{align*}\tan(\pi + \theta)\end{align*}

3. Find the exact value for tan15\begin{align*}\tan 15^\circ\end{align*}

Solutions:

1.

tan75=tan(45+30)=tan45+tan301tan45tan30=1+331133=3+33333=3+3333+33+3=9+63+393=12+636=2+3

2. tan(π+θ)=tanπ+tanθ1tanπtanθ=tanθ1=tanθ\begin{align*}\tan (\pi + \theta) = \frac{\tan \pi + \tan \theta}{1- \tan \pi \tan \theta} = \frac{\tan \theta}{1} = \tan \theta\end{align*}

3.

tan15=tan(4530)=tan45tan301+tan45tan30=1331+133=3333+33=333+33333=9+63+393=12+636=2+3

### Concept Problem Solution

The Concept Problem asks you to find:

tan(12040)\begin{align*}\tan (120^\circ - 40^\circ)\end{align*}

You can use the tangent difference formula:

tan(ab)=tanatanb1+tanatanb

to help solve this. Substituting in known quantities:

tan(12040)=tan120tan401+(tan120)(tan40)=1.732.8391+(1.732)(.839)=2.571.453148=5.674

### Explore More

Find the exact value for each tangent expression.

1. tan5π12\begin{align*}\tan\frac{5\pi}{12}\end{align*}
2. tan11π12\begin{align*}\tan\frac{11\pi}{12}\end{align*}
3. tan165\begin{align*}\tan-165^\circ\end{align*}
4. tan255\begin{align*}\tan255^\circ\end{align*}
5. tan15\begin{align*}\tan-15^\circ\end{align*}

Write each expression as the tangent of an angle.

1. tan15+tan421tan15tan42\begin{align*}\frac{\tan15^\circ+\tan42^\circ}{1-\tan15^\circ\tan42^\circ}\end{align*}
2. tan65tan121+tan65tan12\begin{align*}\frac{\tan65^\circ-\tan12^\circ}{1+\tan65^\circ\tan12^\circ}\end{align*}
3. tan10+tan501tan10tan50\begin{align*}\frac{\tan10^\circ+\tan50^\circ}{1-\tan10^\circ\tan50^\circ}\end{align*}
4. tan2y+tan41tan2tan4y\begin{align*}\frac{\tan2y+\tan4}{1-\tan2\tan4y}\end{align*}
5. tanxtan3x1+tanxtan3x\begin{align*}\frac{\tan x-\tan3x}{1+\tan x\tan3x}\end{align*}
6. tan2xtany1+tan2xtany\begin{align*}\frac{\tan2x-\tan y}{1+\tan2x\tan y}\end{align*}
7. Prove that tan(x+π4)=1+tan(x)1tan(x)\begin{align*}\tan(x+\frac{\pi}{4})=\frac{1+\tan(x)}{1-\tan(x)}\end{align*}
8. Prove that tan(xπ2)=cot(x)\begin{align*}\tan(x-\frac{\pi}{2})=-\cot(x)\end{align*}
9. Prove that tan(π2x)=cot(x)\begin{align*}\tan(\frac{\pi}{2}-x)=\cot(x)\end{align*}
10. Prove that tan(x+y)tan(xy)=tan2(x)tan2(y)1tan2(x)tan2(y)\begin{align*}\tan(x+y)\tan(x-y)=\frac{\tan^2(x)-\tan^2(y)}{1-\tan^2(x)\tan^2(y)}\end{align*}

### Vocabulary Language: English

Tangent Difference Formula

Tangent Difference Formula

The tangent difference formula relates the tangent of a difference of two arguments to a set of tangent functions, each containing one argument.
Tangent Sum Formula

Tangent Sum Formula

The tangent sum formula relates the tangent of a sum of two arguments to a set of tangent functions, each containing one argument.

## Date Created:

Sep 26, 2012

Feb 26, 2015
You can only attach files to Modality which belong to you
If you would like to associate files with this Modality, please make a copy first.

# Reviews

Help us create better content by rating and reviewing this modality.